Boundary-value problem in an infinite layer - Antypko, I. I.; Semenova, N. O. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We establish necessary and sufficient conditions for a nonlocal two-point boundary-value problem in an infinite layer for the equation $$\frac{{\partial ^2 u(x,t)}}{{\partial t^2 }} + P\left( {\frac{\partial }{{\partial x}}} \right)\frac{{\partial u(x + h_1 ,t)}}{{\partial t}} + Q\left( {\frac{\partial }{{\partial x}}} \right)u(x + h_2 ,t) = 0,$$ whereP(s) andQ(s) are polynomials ins∈ℂ m with constant coefficients, to have infinite type and be degenerate.